2019
DOI: 10.1021/acs.joc.8b03143
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Catalyzed Hydrosilylation of 1,3-Diynes with Triorganosilanes: Regio- and Stereoselective Synthesis of Mono- or Bis-silylated Adducts

Abstract: An efficient method has been successfully developed for the functionalization of various 1,3-diynes by the hydrosilylation reaction with triethyl- or triphenylsilane catalyzed by Pt catalysts (Pt2(dvs)3, PtO2, or Pt­(PPh3)4). Comprehensive optimization studies were performed for the first time to find suitable process conditions for the stereo- and regioselective formation of mono- or bis-silylated adducts from commercially available substrates and catalysts. Silyl-substituted 1,3-enynes or bis-silyl-functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…After the reaction, boron moiety was presented at the internal position of the diyne system. The same regioselectivity was also observed for other hydrometallation processes, i. e. hydrosilylation, [28] hydrostannation [29] and hydromagnesiation. [30] In 2015, Yun et al reported the synthesis of borylsubstituted enynes via protoboration of symmetrical and unsymmetrical conjugated diynes with bis(pinacolato)diboron in methanol as a proton source.…”
Section: Introductionsupporting
confidence: 74%
“…After the reaction, boron moiety was presented at the internal position of the diyne system. The same regioselectivity was also observed for other hydrometallation processes, i. e. hydrosilylation, [28] hydrostannation [29] and hydromagnesiation. [30] In 2015, Yun et al reported the synthesis of borylsubstituted enynes via protoboration of symmetrical and unsymmetrical conjugated diynes with bis(pinacolato)diboron in methanol as a proton source.…”
Section: Introductionsupporting
confidence: 74%
“…On the basis of our previous experience [11] and literature reports regarding hydrosilylation of 1,4-disubstituted 1,3-butadiynes with silanes, [12] reactions of nine structurally and electronically different 1,3-diynes (2 a-i) (Scheme 1) with (HSiMe 2 O)(i-Bu) 7 Si 8 O 12 (1) were performed (in the presence of platinum catalysts: Pt 2 (dvs) 3 (Karsted's catalyst), Pt(PPh 3 ) 4 , PtO 2 and Pt/ SDB (SDB-styrene-divinylbenzene copolymer), [10b] in an air atmosphere, without any purification of the acquired chemicals). Processes were carried out at temperatures between 40°C and 100°C or at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Analogue influence of the t -Bu and (CH 3 ) 2 OSi(CH 3 ) 3 groups on forming the product of monohydrosilylation of 1,3-diynes was previously observed. 69 , 70 …”
Section: Resultsmentioning
confidence: 99%